Coping, Negative Cognitive Style and Depressive Symptoms in Children of Depressed Parents - Dunbar, Jennifer P. (2013)
Coping and negative cognitive style were studied in relation to depressive symptoms in children at risk for depression. In a sample of 165 children (ages 9–15) of depressed parents, the main and interaction effects of coping and negative cognitive style were examined in association with children’s depressive symptoms measured by parent and child report on questionnaires and diagnostic interviews. Negative cognitive style was related to three types of coping (primary control, secondary control, and disengagement). Furthermore, coping and negative cognitive style made independent contributions to depressive symptoms. Little support emerged for interactive effects on depressive symptoms. Implications for future research with this high-risk population of children are considered.